Monitoring overtraining in women wrestlers - Tian, Y.; He, Z. (International Journal of Wrestling Science, 2013)
As athletes strive to improve their performance, they invariably increase the frequency, volume and intensity of training. In doing so, they invariably experience fatigue. This fatigue ranges from short-term "normal" fatigue when recovery is achieved within hours or days, to longer-lasting "abnormal" fatigue where recovery is prolonged [29]. This latter aspect of recovery can be divided into a number of distinct duration phases, that include functional overreaching (FOR), non-functional overreaching (NFOR) and the overtraining syndrome (OTS) [30]. Recovery accompanying the FOR state typically occurs within two weeks, is a vital part of training and often utilized by athletes during a typical training cycle prior to a period of recovery. It is further hypothesized that FOR stimulates a super-compensation effect and, as a result, increases performance to a level higher than previously attained [7].